Correlation of Age, Sex, and Symptoms to Number of Problematic Joints in Children with Idiopathic Juvenile Arthritis - Made Retna Paramita Savitri; Azwin Mengindra Putera; Noor Idha Handajani (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Juvenile Idiopathic Arthritis (JIA) is a rare case in Asia, including Indonesia. Objective:Analyze the correlation between age, sex, and symptoms on the number of joint problems in children withJIA symptoms. Methods: This study used a retrospective design from January 2016 to December 2019.The data collecting in this study was included age, sex, symptoms, and the number of joint problems. Theanalysis used was multiple linear regression with p <0.05. Results: The correlation between sex (? = 0.015;95% CI -0.002 – 0.002; p = 0.916), age (? = 0.015; 95% CI -0.197 – 0.291; p = 0.916) to the number ofjoint problems was not significant. While, the correlation between symptoms and the number of joints withproblems was significant, which included swelling (? = 1.012; 95% CI 0.243 – 1.782; p = 0.011), fever(? = 1.000; 95% CI 0.082 – 1.918; p = 0.034), and pain. (? = 0.931; 95% CI 0.082 – 1.918; p = 0.007).Conclusion: There is a significant relationship between symptoms and the number of problem joints whileage and sex are not significant